Review by R.F. Fuchs of Georg Bredig's "Anorganische Fermente" - Fuchs, R.F. (1902)
R.F. Fuchs’ handwritten 1902 article in the Biologisches Centralblatt examines the similarities between colloid solutions and enzymes, with a focus on experiments conducted by Georg Bredig (1868-1944) and colleagues. Published in Germany from 1881-1981, the Biologisches Centralblatt was one of the earliest and most influential biological journals and covered a wide range of topics in biology, such as botany, zoology, microbiology, and physiology.
Keywords: Colloids; Enzymes; Bredig, Georg, 1868-1944; Science publishing